Construction of Chiral alpha-Amino Quaternary Stereogenic Centers via Phase-Transfer Catalyzed Enantioselective alpha-Alkylation of alpha-Amidomalonates - Ha, Min Woo; Lee, Myungmo; Choi, Sujee; Kim, Seek; Hong, Suckchang; Park, Yohan; Kim, Mi-hyun; Kim, Taek-Soo; Lee, Jihoon; Lee, Jae Kyun; Park, Hyeung-geun (AMER CHEMICAL SOC, 2015)
An efficient enantioselective synthetic method for alpha-amido-alpha-alkylmalonates via phase-transfer catalytic alpha-alkylation was successfully developed. The alpha-alkylation of alpha-amidomalonates under phase-transfer catalytic conditions (50% KOH, toluene, -40 degrees C) in the presence of (S,S)-3,4,5-trifluorophenyl-NAS bromide afforded the corresponding alpha-amido-alpha-alkylmalonates in high chemical yields (up to 99%) and optical yields (up to 97% ee), which could be readily converted to versatile chiral intermediates bearing alpha-amino quaternary stereogenic centers. The synthetic potential of this methodology was demonstrated via the synthesis of chiral azlactone, oxazoline, and unnatural alpha-amino acid.
Keywords: BETA-KETO-ESTERS; ASYMMETRIC-SYNTHESIS; ELECTROPHILIC AMINATION; KETOESTERS; ACID; HYDRAZINATION; TRISOXAZOLINE